Synthesis and characterization of poly-L-lysine grafted SBA-15 using NCA polymerization and click chemistry - Kar, Mrityunjoy; Malvi, Bharmana; Das, Anindita; Panneri, Suyana; Sen Gupta, Sayam (Journal of Materials Chemistry, 2011)
Poly-L-lysine (PLL) grafted ordered mesoporous material was prepared by a combination of NCA polymerization and click chemistry. Large pore SBA-15 with a mesopore diameter of similar to 12 nm was synthesized using a previously reported method. The surface of this SBA-15 material was modified with azidopropyl groups. This ``clickable'' SBA-15 was then reacted with an alkyne terminated poly-L-lysine synthesized by the ring-opening polymerization of 3-cbz-L-lysine NCA with N-TMS propargylamine as the initiator. This procedure allows grafting of a uniform polymer film with a high polymer loading. No appreciable pore blocking was observed upon grafting of PLL. No change in the periodic structure of the SBA-15 was observed throughout the grafting process. The SBA-15 PLL conjugate was characterized using (13)C and (29)Si NMR, XRD, FT-IR, N(2) adsorption-desorption and thermogravimetry. The results indicate that polypeptides can be easily grafted onto various ordered mesoporous materials by this ``grafting to'' methodology with accessible pores and high loadings of the polypeptide.

Uptake of Azo dyes into silk glands for production of colored silk cocoons using a green feeding approach - Nisal, Anuya; Trivedy, Kanika; Mohammad, Hasan; Panneri, Suyana; Sen Gupta, Sayam; Lele, Ashish K.; Manchala, Ramesh; Kumar, Nirmal S.; Gadgil, Mugdha; Khandelwal, Harish B.; More, Snehal; Laxman, Ryali Seeta (ACS Sustainable Chemistry & Engineering, 2014)
Dyeing of textile fabrics is considered to be one of the most polluting industries today, and there is a need to develop green processes that can reduce this pollution. A promising technology that can potentially cleanup the dyeing of silk fibers that are widely used for textile applications would involve the generation of intrinsically colored silk cocoons. This can be achieved by feeding of Bombyx mori silkworm larvae with a modified feed of mulberry leaves containing a sprayed dye solution. This process significantly reduces the need for treating toxic dye effluents that are generated in traditional dyeing processes. In this report, we have evaluated a set of seven different azo dyes that are used in the textile industry for dyeing to produce intrinsically dyed silk. The dyes used in the study had similar chemical structures with systematically varying partition coefficients. The results suggest that while some dyes produced intrinsically colored silk other did not. Careful evaluation of the physical properties of these related azo dyes suggest that the balance of hydrophobic and hydrophilic character is necessary for diffusion of the dye from the alimentary canal of the silkworm larva into the hemolymph and later into the silk glands. The partition coefficient of the dye also determines the preferential association of the dye with either sericin or fibroin protein in the silkworm gland and finally into the cocoon. These insights are extremely important in development of novel dye molecules that can be successfully fed to Bombyx mori silkworm larvae for producing intrinsically colored silk of various colors and shades.
Keywords: Azo dyes; Biochemical pathways; Color silk; Dye uptake; `' Green `' silk